11ß Hydroxysteroid Dehydrogenases Regulate Circulating Glucocorticoids but Not Central Gene Expression - Rensel, Michelle A. (Gen Comp Endocrinol, 2021)
Regulation of glucocorticoids (GCs), important mediators of physiology and behavior at rest and during stress, is multi-faceted and dynamic. The 11ß hydroxysteroid dehydrogenases 11ß-HSD1 and 11ß-HSD2 catalyze the regeneration and inactivation of GCs, respectively, and provide peripheral and central control over GC actions in mammals. While these enzymes have only recently been investigated in just two songbird species, central expression patterns suggest that they may function differently in birds and mammals, and little is known about how peripheral expression regulates circulating GCs. In this study, we utilized the 11ß-HSD inhibitor carbenoxolone (CBX) to probe the functional effects of 11ß-HSD activity on circulating GCs and central GC-dependent gene expression in the adult zebra finch (Taeniopygia guttata). Peripheral CBX injection produced a marked increase in baseline GCs 60min after injection, suggestive of a dominant role for 11ß-HSD2 in regulating circulating GCs. In the adult zebra finch brain, where 11ß-HSD2 but not 11ß-HSD1 is expressed, co-incubation of micro-dissected brain regions with CBX and stress-level GCs had no impact on expression of several GC-dependent genes. These results suggest that peripheral 11ß-HSD2 attenuates circulating GCs, whereas central 11ß-HSD2 has little impact on gene expression. Instead, rapid 11ß-HSD2-based regulation of local GC levels might fine-tune membrane GC actions in brain. These results provide new insights into the dynamics of GC secretion and action in this important model organism.